The Role of Teachers in Addressing Beginning Reading Difficulties Among First-Grade Students at SD Negeri 1 Tanjung Sari Tirtomoyo - Oney Putri Fedika Sari; Meidawati Suswandari (Journal of Educational Learning and Innovation (ELIa), 2025)
This research aims to describe the role of teachers in overcoming reading problems at the beginning of class I students of SD Negeri 1 Tanjung Sari. This type of research uses descriptive-qualitative. The subject of this research is the first class teacher of Tanjung Sari State Elementary School 1. Data collection tools used for observation, interview, and documentation. This research data analysis technique is interactive analysis which includes data collection, data presentation, and conclusion. Research results show that the role of teachers in overcoming reading problems at the beginning of students in grade 1 of SD Negeri 1 Tanjung Sari is, as a mentor, coach, and companion for student learning activities. In his role as a mentor, the teacher tries to guide students so that they can find various talents they have, especially the talent in reading the beginning. As a teacher trainer, they train students in the formation of basic competencies, according to their respective talents. As a companion, the teacher accompanies and controls the students in the classroom so that the things conveyed in the process of teaching and learning activities can be carried out properly.